Tetrachloroethene Dehalogenase from Dehalospirillum multivorans: Cloning, Sequencing of the Encoding Genes, and Expression of the pceA Gene in Escherichia coli - Neumann, Anke (American Society for Microbiology, 1998)
The genes encoding tetrachloroethene reductive dehalogenase, a corrinoid-Fe/S protein, of Dehalospirillum multivorans were cloned and sequenced. The pceA gene is upstream of pceB and overlaps it by 4 bp. The presence of a ς70-like promoter sequence upstream of pceA and of a ρ-independent terminator downstream of pceB indicated that both genes are cotranscribed. This assumption is supported by reverse transcriptase PCR data. The pceA and pceB genes encode putative 501- and 74-amino-acid proteins, respectively, with calculated molecular masses of 55,887 and 8,354 Da, respectively. Four peptides obtained after trypsin treatment of tetrachloroethene (PCE) dehalogenase were found in the deduced amino acid sequence of pceA. The N-terminal amino acid sequence of the PCE dehalogenase isolated from D. multivorans was found 30 amino acids downstream of the N terminus of the deduced pceA product. The pceA gene contained a nucleotide stretch highly similar to binding motifs for two Fe(4)S(4) clusters or for one Fe(4)S(4) cluster and one Fe(3)S(4) cluster. A consensus sequence for the binding of a corrinoid was not found in pceA. No significant similarities to genes in the databases were detected in sequence comparisons. The pceB gene contained two membrane-spanning helices as indicated by two hydrophobic stretches in the hydropathic plot. Sequence comparisons of pceB revealed no sequence similarities to genes present in the databases. Only in the presence of pUBS 520 supplying the recombinant bacteria with high levels of the rare Escherichia coli tRNA(4)(Arg) was pceA expressed, albeit nonfunctionally, in recombinant E. coli BL21 (DE3).